From conversation to collaboration: AI-powered pedagogy and the ethics of speak-bot - Veni Nella Syahputri; Nyak Mutia Ismail; Cut Nabilla Kesha (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2026)
This paper explores the pedagogical innovation and ethical considerations of integrating SPEAK-BOT, a chatbot-assisted learning framework, into collaborative speaking classrooms. SPEAK-BOT is introduced as a framework for supporting conversation-based speaking practice through structured interaction between students, peers, and chatbot-assisted prompts. Rather than replacing classroom communication, the framework is intended to provide additional opportunities for learners to practice speaking, exchange ideas, and respond to guided conversational tasks. In this study, the potential value of SPEAK-BOT is examined through a design-oriented analysis of its learning steps, interaction patterns, and classroom applicability. This study employed a qualitative Design and Development Research (DDR) approach involving 25 undergraduate students enrolled in a speaking course and 4 English lecturers, using teacher reflection logs, learner self-assessment questionnaires, and chatbot interaction records that were analyzed thematically to examine how the SPEAK-BOT framework operated in classroom speaking practice. Data sources include teacher feedback, learner self-assessment, and AI-generated responses. Findings suggest that SPEAK-BOT enhances learner engagement, encourages risk-taking in language use, and supports real-time feedback loops that are often challenging for teachers to provide individually. At the same time, the research identifies critical ethical dimensions: dependency on AI, the risk of misrepresentation, and the need for responsible data use. These issues highlight the importance of developing digital literacy and critical awareness alongside language skills.